IMPLEMENTASI REDUNDANT LINK UNTUK MENGATASI DOWNTIME DENGAN METODE FAILOVER - Adhiwibowo, Whisnumurti; Irawan, Ahmad Rudi (Jurnal Pengembangan Rekayasa dan Teknologi, 2019)
Network failure not only affects performance, but also affects individuals or industries. Network Downtime can occur for many reasons, the most common is cable damage and network configuration. This condition requires a more reliable network that is not susceptible to network interference. One of the most important aspects of ensuring that network is redundancy. The method to get high is to build a backup system that will still work if it happens on the main system. Redundancy with failover can be a solution when downtime occurs on nodes in the network. Failover is a process of transferring connections to an alternative path caused by a system or hardware or network interruption or abnormality. The implementation method used is the PPDIOO method which has the stages Prepare, Plan, Design, Implement, Operate and Optimize. System implementation simulations are made using GNS3 software. This design will result in the merging of two networks from different ISP, using MikroTik routers and The Dude monitoring applications that are very useful for troubleshooting network problems in CV. Cahaya Alam.